Zinc Supplementation Dosage Variations to Metallothionein Protein Level of Rattus Norvegicus - Budi Santosa; Hertanto Wahyu Subagyo; Lisyani S; Henna Rya Sunoko (International Journal of Science and Engineering, 2013)
Zinc is an essential trace element involving in the activity of more than 300 enzymes and proteins of human body. One important role of zinc is to improve metallothionein protein binding heavy metals and functioning as heavy metal detoxification facilities. This research discusses the effect of zinc supplement  on the  improvement of metallothionein protein level. The in vivo test involving 28 rats categorized in 4 groups was performed. The experiments used randomized post test control group design. The 3 groups were daily supplemented by zinc in th concentration of  0.2 mg, 0.4 mg, and 0.8 mg. Whereas, the last group was let without zinc treatment. As an indicator the metallothionein protein level was checked after three weeks. The data was then evaluated by Anova an Bonferroni test in order to know the signicant of protein level difference among the groups. The result showed that the average of metallothionein protein level improved by increasing zinc suppplement with the 0.95 ±0.20; 1.28 ±0.19; 1.39 ±0.09; 1.91 ±0.3 ng/ml metallothionein per 0, 0,2, 0,4, 0,8.mg zinc added. Based on the ANOVA and Bonferroni test,  indicated that the improvement was significant as shown with p value  of 0.00